Neutrophil‐lymphocyte ratio and a dosimetric factor for predicting symptomatic radiation pneumonitis in non‐small‐cell lung cancer patients treated with concurrent chemoradiotherapy. (28th June 2017) - Lee, Yun Hee; Choi, Hoon‐Sik; Jeong, Hojin; Kang, Ki Mun; Song, Jin Ho; Lee, Won Sup; Lee, Gyeong‐Won; Song, Haa‐Na; Kim, Hoon‐Gu; Kang, Myoung Hee; Rhee, Dong Yoon; Jeong, Bae Kwon
Abstract: Objectives: To identify the factors that predict the progression of radiological radiation pneumonitis (RP) to symptomatic RP, and to evaluate the usefulness of the neutrophil‐lymphocyte ratio (NLR) as a marker of RP severity and prognosis in stage III non‐small cell lung cancer (NSCLC) patients treated with definitive concurrent chemoradiotherapy (CCRT). Materials and Methods: We retrospectively reviewed 61 patients treated between January 2010 and December 2015. Patients' demographic characteristics, clinical data, laboratory findings and treatment parameters were analyzed to determine the predictive factors associated with progression from radiological RP to symptomatic RP. Results: Forty‐seven patients (77%) exhibited radiological RP at a median of 78 days after radiation therapy (RT) completion, and 15 (32%) of these patients developed symptomatic RP. The interval between RT completion and radiological RP presentation was shorter in patients who progressed to symptomatic RP ( P = .001); progression was highly probable if this latency period was ≤2 months ( P = .002). Stage and RT technique correlated with symptomatic RP development ( P = .046 and P = .046, respectively). Among dosimetric factors, a V20 (defined as the lung volume receiving ≥20 Gy) of >30% was the most significant predictor of symptomatic RP ( P = .001). The NLR and C‐reactive protein level at radiological RP were higher in patients who developed symptomatic RP ( P = .067 and P = .012, respectively). On multivariate analysis, a V20 >30% and an NLR at radiological RP >6 were associated with symptomatic RP development. Conclusion: The NLR at radiological RP is a useful biomarker for predicting symptomatic RP development after CCRT in stage III NSCLC patients.